DAMPAK USAHA KEGIATAN PENAMBANGAN PASIR TERHADAP PERUBAHAN MATA PENCAHARIAN DI KABUPATEN MUNA BARAT - Irfan Ido (Universitas Halu Oleo, 2019)
ABSTRACTTondasi Village is one of the Villages in the North Tiworo Sub-District West Muna District as a producer of sand extraction. This study aims to find out: (1) Sand mining business in Tondasi Village, North Tiworo District, West Muna Regency; (2) Determine what factors cause people to change their livelihood patterns. The sample in this study used the Non Probability Sampling technique that was chosen which was saturated sampling (census). In this study, the samples taken were 229 Tondasi villagers. Data were analyzed with 3 stages, namely data reduction, data presentation and conclusion. The results of this study show that sand mining in Tondasi Village initially used traditional tools, but technological development is increasingly rapid, so sand mining in Tondasi Village uses a sand suction machine. There are 3 factors that cause the community to change their livelihood to become sand miners, namely the income factor, the lack of catches for the people who are fishermen background, and the failure of the crop due to uncertain seasonal factors for the people who are farmers. However, there are 3 factors that have caused the community to leave their livelihood as sand miners, namely the emergence of new technology to mine the sand which makes traditional sand miners unable to compete with miners who use vacuum cleaners, the absence of mining permits from the government and the emergence of awareness about the importance of protecting the environment.Keywords: Sand Mining Business, Livelihood Changes